1999
DOI: 10.1002/hep.510290204
|View full text |Cite
|
Sign up to set email alerts
|

Brain Histamine Levels and Neocortical Slow–Wave Activity in Rats With Portacaval Anastomosis

Abstract: To determine whether the increased histamine levels in the brain of rats with portacaval anastomosis (PCA) are associated with the development of sleep disturbances during the light phase, the neocortical slow-wave activity of PCA-operated rats was examined with electroencephalography (EEG) 1 month and 6 months after the surgery. The tissue levels of histamine, tele-methylhistamine, 5-hydroxytryptamine (5-HT) (serotonin), and 5-hydroxyindole-3-acetic acid (5-HIAA) in frontal cortex were assayed by high-perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[6][7][8] Relating the functions controlled by histamine to the clinical presentation of HE, it appears a priori that histamine could participate in the pathogenesis of the sleep disturbances, decreased spontaneous voluntary movement, and increased plasma prolactin levels in patients with HE and in the hormonal changes, growth retardation, and the altered vigilance, locomotor activity, and circadian rhythmicity in rats with PCA. Consistent with these possibilities, we have previously shown that blockade of central histamine H 1 receptors with the specific antagonist, pyrilamine (mepyramine), restores the altered circadian rhythmicity of feeding and locomotor activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Relating the functions controlled by histamine to the clinical presentation of HE, it appears a priori that histamine could participate in the pathogenesis of the sleep disturbances, decreased spontaneous voluntary movement, and increased plasma prolactin levels in patients with HE and in the hormonal changes, growth retardation, and the altered vigilance, locomotor activity, and circadian rhythmicity in rats with PCA. Consistent with these possibilities, we have previously shown that blockade of central histamine H 1 receptors with the specific antagonist, pyrilamine (mepyramine), restores the altered circadian rhythmicity of feeding and locomotor activity.…”
mentioning
confidence: 99%
“…Among the least exploited consequences of HE are the marked changes in the brain histaminergic system, which have been previously documented both in patients with HE 3 and in rats with portacaval anastomosis (PCA), a well-established animal model of the disease. [4][5][6][7][8] There is substantial evidence that histamine acts as a neurotransmitter in mammalian brain. 9 Histaminergic neurons are located exclusively in the tuberomammillary nucleus of the posterior hypothalamus and send their varicose fibers to almost every region of the brain.…”
mentioning
confidence: 99%
“…PSE has been described as a disorder of multiple neurotransmitter systems. 13 Specifically, the histaminergic synaptic imbalance, which becomes apparent shortly 14,15 and persists for at least 8 months after surgery, 12,[16][17][18] is among the most interesting consequences of portacaval shunting in the rat.…”
mentioning
confidence: 99%
“…12,17,18 These rats have excessively high tissue levels of histamine in brain regions particularly enriched in histaminergic neurons and/or cell bodies. 12,17 Furthermore, the spontaneous, as well as the depolarizationinduced and pharmacologically induced histamine release from anterior hypothalamus are significantly increased in these rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation